Biodistribution Profile of Magnetic Nanoparticles in Cirrhosis-Associated Hepatocarcinogenesis in Rats by AC Biosusceptometry - Soares, Guilherme A. [UNESP]; Pereira, Gabriele M. [UNESP]; Romualdo, Guilherme R. [UNESP]; Biasotti, Gabriel G. A. [UNESP]; Stoppa, Erick G. [UNESP]; Bakuzis, Andris F.; Baffa, Oswaldo; Barbisan, Luis F. [UNESP]; Miranda, Jose R. A. [UNESP] (MDPI, 2022)
Since magnetic nanoparticles (MNPs) have been used as multifunctional probes to diagnose and treat liver diseases in recent years, this study aimed to assess how the condition of cirrhosis-associated hepatocarcinogenesis alters the biodistribution of hepatic MNPs. Using a real-time image acquisition approach, the distribution profile of MNPs after intravenous administration was monitored using an AC biosusceptometry (ACB) assay. We assessed the biodistribution profile based on the ACB images obtained through selected regions of interest (ROIs) in the heart and liver position according to the anatomical references previously selected. The signals obtained allowed for the quantification of pharmacokinetic parameters, indicating that the uptake of hepatic MNPs is compromised during liver cirrhosis, since scar tissue reduces blood flow through the liver and slows its processing function. Since liver monocytes/macrophages remained constant during the cirrhotic stage, the increased intrahepatic vascular resistance associated with impaired hepatic sinusoidal circulation was considered the potential reason for the change in the distribution of MNPs.
Keywords: AC biosuceptometry; cirrhosis-associated rat hepatocarcinogenesis; magnetic nanoparticles; nanotechnology